2018
DOI: 10.12973/iji.2018.11411a
|View full text |Cite
|
Sign up to set email alerts
|

In-service Teacher Training: Problems of the Teachers as Learners

Abstract: Teachers need to update their knowledge and skills on curricula, psychology, and pedagogy of the learners and new research on teaching and learning; hence, they need appropriate in-service training, as well. However, the professional development practices in which they participate are mostly irrelevant to what they need and stay just in theory. Current researches criticized the inadequacy and inappropriateness of the traditional methods of teachers' professional development. In this research, the views and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…Learning a language represents a challenging and complex process of mastering language systems and skills (Brković, Kardum, & Togonal, 2021;Hundarenko, 2019;Kapranov, 2019;Mulyadi, Arifani, Wijayantingsih & Budiastuti, 2020;Sides & Cuevas 2020;Stognieva, 2020;Štubňa, 2019). Undeniably, language teachers occupy a substantial role in delivering success to language teaching environments (Başal, 2014;Tuncel & Çobanoğlu, 2018). Foreign language students and teachers may have rather similar or different attitudes towards effective language teaching, and the intersection of the two sets has implications for language learning and the effectivity of teaching (Moradi & Sabeti, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Learning a language represents a challenging and complex process of mastering language systems and skills (Brković, Kardum, & Togonal, 2021;Hundarenko, 2019;Kapranov, 2019;Mulyadi, Arifani, Wijayantingsih & Budiastuti, 2020;Sides & Cuevas 2020;Stognieva, 2020;Štubňa, 2019). Undeniably, language teachers occupy a substantial role in delivering success to language teaching environments (Başal, 2014;Tuncel & Çobanoğlu, 2018). Foreign language students and teachers may have rather similar or different attitudes towards effective language teaching, and the intersection of the two sets has implications for language learning and the effectivity of teaching (Moradi & Sabeti, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…He, further, says that the questions teachers ask decide the way in which their students' thinking goes. Ayvaz-Tuncel & Çobanoğlu (2018) believe that teachers need to reflect their own pedagogical competence including planning to the evaluation process at the classroom context. The statement is in line with Moodley (2015) who says that the quality of teachers is measured by their performance in developing good assessment tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that direct training may be superior to indirect training for increasing the probability that teachers acquire proper skills and maintain implementation over time (e.g., Dufrene et al, 2014 ; Sterling-Turner et al 2002 ; Stormont et al, 2007 ). To ensure teachers maintain skills over time, training should be a continuous and direct process (Ayvaz-Tuncel and Çobanoğlu 2018 ).…”
mentioning
confidence: 99%